THE EFFECT OF SALES PROMOTIONS AND TARIFFS ON CONSUMER LOYALTY (CASE STUDY OF GRAB COMPANIES IN BANDUNG CITY) - Wiguna, Evangelius Hans; Padmakusumah, Rizal Ramdan (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2023)
Research conducted on Grab in the city of Bandung was conducted to determine and analyze the effect of sales promotions and tariffs on consumer loyalty. The independent variables in this study are sales promotions and tariffs. While the dependent variable used is consumer loyalty. The research method used in this research is a verification method to find out the relationship between two variables and to do the test using IBM Statistics 25 SPSS. The population in this study are people who live in the city of Bandung and use the Grab application. In this study, the sampling method used is the nonprobability sampling method. The sampling technique in this study used a purposive sampling technique, which means that the sample was taken because of certain considerations. The criteria that must be owned to determine the sample for this study are having an account in the Grab application, domiciled in the city of Bandung and having used online transportation services from Grab at least once. The number of samples in this study was determined using multiple regression data analysis techniques with an error rate of 5%, the sample in this study was determined by 100 people.